2007
DOI: 10.1021/ol071292c
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Conjugate Addition of Formaldehyde N,N-Dialkylhydrazones to β,γ-Unsaturated α-Keto Esters

Abstract: (1S,2R)-1-Aminoindan-2-ol-derived thioureas behave as efficient H-bonding organocatalysts for the nucleophilic conjugate addition of formaldehyde hydrazones to beta,gamma-unsaturated alpha-keto esters as enoate surrogates, affording the corresponding adducts in good yields and enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 22 publications
5
58
0
Order By: Relevance
“…[6] Another relevant example involves oxazol-5A C H T U N G T R E N N U N G (2 H)-ones as aryloyl anion equivalents in the conjugate addition to enoylphosphonates, [7] which also relies on Brønsted-acid catalysis. In addition, one report by Enders uses a-aminonitriles as Michael donors in the enan- tioselective b-glyoxylation of a,b-unsaturated aldehydes under iminium catalysis, which proceeded with enantioselectivities of about 85 % ee, to give the final 1,4-dicarbonyl compounds in moderate overall yield.…”
Section: In Memory Of Our Colleague and Friend Rafael Suaumentioning
confidence: 99%
“…[6] Another relevant example involves oxazol-5A C H T U N G T R E N N U N G (2 H)-ones as aryloyl anion equivalents in the conjugate addition to enoylphosphonates, [7] which also relies on Brønsted-acid catalysis. In addition, one report by Enders uses a-aminonitriles as Michael donors in the enan- tioselective b-glyoxylation of a,b-unsaturated aldehydes under iminium catalysis, which proceeded with enantioselectivities of about 85 % ee, to give the final 1,4-dicarbonyl compounds in moderate overall yield.…”
Section: In Memory Of Our Colleague and Friend Rafael Suaumentioning
confidence: 99%
“…By using in this case β,γ-unsaturated α-keto esters 297 as enoate surrogates, it was found that the addition of 51k was strongly accelerated by catalytic amounts of thioureas. The best results in terms of selectivity were achieved by employing (1S,2R)-aminoindan-2-ol-derived thiourea 298, [136] which led to adducts 299 in good yields and enantioselectivities (Scheme 54). [137] These compounds are versatile 1,4-dicarbonyl compounds that can be transformed into nitriles 300 by MMPP·6H 2 O. Additionally, ozonolytic cleavage of 299 (R = Me) afforded an unstable intermediate that was further oxidized by a HCO 2 H/H 2 O 2 mixture and treated with SOCl 2 /MeOH to obtain succinate 301 resulting from deoxidative decarboxylation.…”
Section: Activation By Brønsted Acids or H-bonding Organocatalystsmentioning
confidence: 99%
“…However,c ompared with a,b-unsaturated ketones and nitroalkene, b,g-unsaturated a-keto esters as Michael acceptors are limited. [11] The asymmetric addition of 1,3-difunctionald onors to b,g-unsaturated-a-ketoesters catalyzed by organocatalysts [11b-p] and chiralm etal catalysts basedo nc opper, [11r] nickel, [11s] yttrium, [11t] and zinc [11u] has received intense attention,b ecause the reaction can follow ad omino acetalization to construct ac hiral six-membered oxygenated heterocycle. Retrosynthetically,achiral five-membered oxygen heterocycle can be formed throught he reaction of b,g-unsaturateda-ketoester with 1,2-difunctional compound such as a-hydroxyacetophenone, which has acted as donor in the Michael addition of a,b-unsaturated ketones or nitroalkenes.…”
mentioning
confidence: 99%
“…After 30 min, the reaction afforded the anti-product in 63 %i solated yield ( 13 CNMR spectrar evealed that major product anti-3a was obtained as an equilibrating mixture of anomers (about 2:1) caused by 2-OH and 2-COOCH 3 .T hese anomers equilibrated slowly enough so as to appear as separatec ompounds in 1 Ha nd 13 CNMR spectra but quickly enough that they did not resolve by chromatography.T he trace of the racemic anti-3a on ac hiral HPLC column showed only one pair of peaks for the two enantiomers. [11,14] However,t he minor synproduct was ar apid equilibrium between the cyclic hemiketal syn-3a and the Michael-typeproduct syn-3a'. [15] As eries of ligandsw ere then examined and the results are summarized in Ta ble 1.…”
mentioning
confidence: 99%